Bioresorbable Electronics: Anhydride‐Assisted Spontaneous Room Temperature Sintering of Printed Bioresorbable Electronics (Adv. Funct. Mater. 29/2020). (16th July 2020) - Li, Jiameng; Xu, Hang; Zhang, Zian; Hao, Yafeng; Wang, Hanjie; Huang, Xian
Abstract : In article number 1905024, Hang Xu, Xian Huang, and co‐workers present a novel approach to achieve high performance flexible bioresorbable electronic devices using Zn nanoparticles and an anhydride‐assisted room‐temperature water sintering process. The resulting devices work stably in air for a prolonged time and disappear in liquid environments within a controllable dissolution time, facilitating rapid and sustainable recycling of electronic components.